Thermal performance under constant temperatures can accurately predict insect development times across naturally variable microclimates - von Schmalensee, Loke; Hulda Gunnarsdóttir, Katrín; Näslund, Joacim; Gotthard, Karl; Lehmann, Philipp (Dryad, 2021)
External conditions can drive biological rates in ectotherms by directly
influencing body temperatures. While estimating the temperature dependence
of performance-traits such as growth and development rate is feasible
under controlled laboratory settings, predictions in nature are difficult.
One major challenge lies in translating performance under constant
conditions to fluctuating environments. Using the butterfly Pieris napi as
model system, we show that development rate, an important fitness trait,
can be accurately predicted in the field using models parameterized under
constant laboratory temperatures. Additionally, using a factorial design,
we show that accurate predictions can be made across microhabitats, but
critically hinge on adequate consideration of nonlinearity in reaction
norms, spatial heterogeneity in microclimate, and temporal variation in
temperature. Our empirical results are also supported by a comparison of
published and simulated data. Conclusively, our combined results suggest
that, discounting direct effects of temperature, insect development rates
are generally unaffected by thermal fluctuations.
Thermal performance in development rate was measured at 8 constant
temperatures in the butterfly Pieris napi. Measurements were made for eggs
and larvae separately, as well as for the full ontogonetic development
between oviposition and pupation (eggs and larvae combined). Thermal
performance curves were fit to the data. Prediction models were
parameterized based on this data, and validated through field transplants.
For the field transplants, microclimate temperatures were frequently
sampled at multiple sites. These temperatures were used to predict
development times. For comparison, weather station data was also used in
the prediction model. Transplanted individuals were monitored and their
development times in the field were compared to predictions. All raw data
necessary to reproduce these results are available here, and compressed to
"von_Schmalensee_et_al_2021_ecol_lett_scripts_and_data.rar".
Additionally, the scripts used to produce the results and the five main
figures are available, with annotation. See the "0_readme.txt"
file for more information, and the main manuscript and supporting
information for a detailed description of the methods.
All raw data necessary to reproduce these results are available here, and
compressed to
"von_Schmalensee_et_al_2021_ecol_lett_scripts_and_data.rar".
Additionally, the scripts used to produce the results and the five main
figures are available, with annotation. See the "0_readme.txt"
file for more information, and the main manuscript and supporting
information for a detailed description of the methods.
Keywords: FOS: Biological sciences; field transplant; model fitting; prediction modelling